Long‐term follow‐up of lung transplant recipients supports non‐operative treatment of uncomplicated diverticulitis. Issue 10 (27th September 2016) - Vetter, Diana; Schuurmans, Macé M.; Benden, Christian; Clavien, Pierre‐Alain; Nocito, Antonio
Abstract: Background: We aim to assess the incidence, current treatment, and outcome of diverticulitis in highly immunosuppressed lung transplant recipients. Methods: Retrospective analysis of a prospective database of 403 lung transplant recipients transplanted between 1992 and 2013 with a mean follow‐up of 100 months (SD 58.0). Results: 4.46% of lung transplant recipients (n=18) developed diverticulitis. Eight lung transplant recipients developed uncomplicated diverticulitis, which were all treated successfully with antibiotics. Three patients (37.5%) underwent elective sigmoid resection with severe Grade 3b complications after two of five (40%) surgical procedures. Diverticulitis recurrence occurred in five patients (60%). In total, 10 lung transplant recipients presented with 11 episodes of perforated diverticulitis with a 30‐day mortality rate of 9.1%. Hartmann procedure was performed in eight lung transplant recipients. Sigmoid resection with primary anastomosis and protective ileostomy was performed in three patients with Hinchey I. Two of these patients developed anastomotic leakage with a secondary Hartmann procedure. Conclusion: Due to high leakage rate after resection with primary anastomosis and protective ileostomy in our cohort of lung transplant recipients with perforated diverticulitis, the Hartmann procedure seems to be the safer option. In contrast, in uncomplicated diverticulitis, non‐operative treatment can be considered as a safe and highly successful treatment option, even for recurrences.